Penentuan Umur Simpan Produk Whitening Mask Powder Dengan Metode Accelerated Shelflife Testing Model Labuza - Saragih, Theofilus Bezaliel Febrian; Anggreni, Anak Agung Made Dewi; Suwariani, Ni Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2025)
Shelf life is the distance of time from when the product is packaged or produced to when the product is still safe to use. This research aims to determine the characteristics of water sorption isotherms (ISA) of whitening mask powder products and to determine the shelf life of whitening mask powder products. The implementation of research in determining shelf life is determined through 2 stages, namely determining the characteristics of water sorption isotherms (ISA) and determining the estimated shelf life with the Accelerated Shelf Life Testing (ASLT) method of the Labuza Model. The parameters used in the calculation of the Labuza Model are equilibrium moisture content (me), initial moisture content (mi), critical moisture content (mc), water vapor permeability (k/x), packaging cross-sectional area (A), product weight, saturated vapor pressure (Po), curve slope (b). The results showed that the characteristics of the water sorption isotherm curve of whitening mask powder products are type II or sigmoid and the shelf life of whitening mask powder products, namely products packaged as much as 100g using polypropylene packaging with a thickness of 0.03 mm and a cross-sectional area of 13 cm x 9.5 cm, get an estimated shelf life of 63.27 days (2.1 months), while for products packaged 100 g using polyethylene packaging with a thickness of 0.13 mm and a cross-sectional area of 13cm x 9.5 cm, get an estimated shelf life of 275 days (9.16 months).